Relación entre el empleo formal y el impuesto a la renta en Loreto periodo 2016 – 2023 - Coronado Padron, María Esther (2025)
This research analyzes the relationship between formal employment and income tax in the department of Loreto during the period 2016-2023. Through a quantitative approach and using Spearman's correlation coefficient, we sought to determine whether the increase in formal employment positively impacts income tax collection. The results indicate a moderate positive correlation between both variables, suggesting that the growth of formal employment contributes to increasing tax collection. However, decreasing trends were identified in both formal employment and income tax collection, which shows structural challenges in Loreto's economy, particularly in terms of high labor informality and tax evasion. The study concludes that the formalization of employment is key to improving tax revenues, but that more effective public policies are required to promote formal employment and improve the tax culture in the region. The recommendations include strengthening incentives for formalization and improving tax infrastructure, while the proposals point to the implementation of support programs for microbusinesses and the use of technologies for inspection.